The marketing edge for filmmakers : developing a marketing mindset from concept to release - Schwartz, Russell, approximately 1948-; MacDonald, Katherine, 1980- (American Film Market presents., 2020)
"Written for working and aspiring filmmakers, directors, producers and screenwriters, The Marketing Edge for Filmmakers walks through every stage of the marketing process--from concept to post-production--and illustrates how creative decisions at each stage will impact the marketability of a film. In this book, marketing experts Schwartz and MacDonald welcome you behind the curtain into the inner workings of a studio marketing department and track films of different budgets (studio, genre, independent, and documentary) through the marketing process, examining how each discipline will approach your film. Featuring interviews with both marketers and filmmakers throughout, an extensive glossary and end-of-chapter exercises, The Marketing Edge for Filmmakers offers a unique introduction to film marketing and a practical guide for understanding the impact of marketing on your film"--